Makna dan Persepsi Masyarakat Aceh terhadap Pengobatan Tradisional ‘Rajah Teukijot’ - Tausya, Resi Syahrani; Perangin-angin, Alemina Br. (Aksara: Jurnal Bahasa dan Sastra, 2025)
This research aims to explore the meaning and perception of the people of Cot Lagan Village towards Traditional Medicine 'Rajah Teukijot' and see its relationship with modern medical treatment. The research method used is descriptive qualitative with reader response approach. Data were obtained through interviews with local shamans, questionnaires distributed to the local community, and content analysis of the 'Rajah Teukijot' mantra text. The results show that most of the people of Cot Lagan Village are familiar with the Traditional Medicine 'Rajah Teukijot' and many have tried it with positive changes in their health. Although there are differing views on its effectiveness compared to modern medical treatment, this traditional medicine is considered to have an important spiritual dimension in its understanding and practice. The community also highlights the importance of preserving this cultural practice as part of Aceh's cultural heritage. In conclusion, Traditional Medicine 'Rajah Teukijot' has a deep meaning in Acehnese culture and is considered an important means of treatment. Community perceptions reflect a diversity of views on medicine, spirituality and the importance of preserving cultural heritage. Keywords: Traditional Medicine, Rajah Teukijot, Aceh